The stromal cell-surface protease fibroblast activation protein-α localizes to lipid rafts and is recruited to invadopodia - Knopf, Julia Daniela; Tholen, Stefan; Koczorowska, Maria M.; De Wever, Olivier; Biniossek, Martin L.; Schilling, Oliver (Biochimica et biophysica acta. Molecular cell research, 2015)
Fibroblast activation protein alpha (FAPα) is a cell surface protease expressed by cancer-associated fibroblasts in the microenvironment of most solid tumors. As there is increasing evidence for proteases having non-catalytic functions, we determined the FAPα interactome in cancer-associated fibroblasts using the quantitative immunoprecipitation combined with knockdown (QUICK) method. Complex formation with adenosin deaminase, erlin-2, stomatin, prohibitin, Thy-1 membrane glycoprotein, and caveolin-1 was further validated by immunoblotting. Co-immunoprecipitation (co-IP) of the known stoichiometric FAPα binding partner dipeptidyl-peptidase IV (DPPIV) corroborated the proteomic strategy. Reverse co-IPs validated the FAPα interaction with caveolin-1, erlin-2, and stomatin while co-IP upon RNA-interference mediated knock-down of DPPIV excluded adenosin deaminase as a direct FAPα interaction partner. Many newly identified FAPα interaction partners localize to lipid rafts, including caveolin-1, a widely-used marker for lipid raft localization. We hypothesized that this indicates a recruitment of FAPα to lipid raft structures. In density gradient centrifugation, FAPα co-fractionates with caveolin-1. Immunofluorescence optical sectioning microscopy of FAPα and lipid raft markers further corroborates recruitment of FAPα to lipid rafts and invadopodia. FAPα is therefore an integral component of stromal lipid rafts in solid tumors. In essence, we provide one of the first interactome analyses of a cell surface protease and translate these results into novel biological aspects of a marker protein for cancer-associated fibroblasts.